PENGARUH VARIASI TEMPERATUR CURING TERHADAP BAGIAN TAK LARUT DAN HILANG PIJAR SEMEN GEOPOLIMER BERBASIS TANAH NAPA PESISIR SELATAN - ,, Narita (RC-INSTITUT, 2019)
Geopolymer cement is produced from minerals containing large amounts of alumina and silica with high reactivity alkaline solutions. One material that contains these elements is napa soil. Based on the XRF analysis conducted by Mawardi (2018) that napa soil has a very high content of SiO2 and Al2O3 with a percentage of 63.20% and 16.55% respectively, so it can be used as a base material in the manufacture of geopolymer cement. In this study testing of lossof ignation (loi) and insoluble parts of cement geopolymer with variations in curing temperature 20ºC, 40ºC, 60ºC, and 80ºC for 8 hours using an oven. Based on the results of the study, the optimum levels of loi and insoluble parts were obtained at a temperature of 60ºC, namely 18% and 19.96%. In soil-based geopolymer cement, the level of loi andinsoluble parts is higher than ordinary cement based on SNI because the SiO2 content in geopolymer cement is very high.